Editorial - Clavijo, Amparo (Colombian Applied Linguistics Journal, 2006)
We are pleased to present to the academic community the number eighth of the Colombian Applied Linguistics Journal which is the product of hard work of the Editorial Committee, the collaboration of our faculty and students of the Masters Program in Applied Linguistics, and the invaluable support of the national and international evaluators of the articles. Whe are thankful to all the people in the Office of Publications at Universidad Distrital because they have worked closely with us every year to make the CJAL a successful project and a high quality publication of the School of Sciences and Education at Universidad Distrital.